Benign Multicystic Peritoneal Mesothelioma as a Rare Cause of Death. (9th November 2022) - Webber, M; Connor, E; Singh, A; Majari, G; moroz, K; craig, R
Abstract: Introduction/Objective: Benign multicystic peritoneal mesothelioma (BMPM) is a tumor arising from the serosa of the peritoneal cavity, often in the pelvis, and is comprised of multiple cysts lined by bland mesothelial cells. It is a rare entity with less than 200 cases reported. The clinical course is often indolent with nonspecific symptoms. It has a strong predilection for females (90%) and is commonly associated with endometriosis or prior surgeries. A high local recurrence rate (50%) following excision has been reported, but malignant transformation is rare. Methods/Case Report: The decedent was a 53-year-old male with a history of multiple hernia repairs who presented following three days of diffuse abdominal pain and obstipation. Imaging showed large volume, complex ascites with multiple rim-enhancing fluid collections, diffuse peritoneal thickening, and a soft tissue density in the lower abdomen/pelvis. Exploratory laparotomy was congruent and revealed 2L of purulent ascites, numerous peritoneal cystic lesions, and a bulky tumor in the pelvis. Blood and ascites cultures later grew Bacteroides species, and Escerichia coli was also isolated from the blood. Postoperatively, the decedent continued to decline, and death occurred the following day. Autopsy demonstrated that the firm pelvic mass entrapped the bladder, rectum, and segments of the small intestine. Sectioning revealed numerous cystic spaces of varying size. Microscopically, they were lined by a single layer of benign cells with mild to focally moderate atypia. These cells stained positive for Calretinin, Pan-cytokeratin, and D2-40 and negative for CD31, which is characteristic of mesothelial cells. These findings are consistent with BMPM. Results (if a Case Study enter NA): NA. Conclusion: The decedent's death is the result of sepsis following acute peritonitis due to BMPM. Death resulting from this entity is exceedingly rare, and to our knowledge this case is only the second reported death due to BMPM.